Clinical Characteristics and Treatment Outcomes of Myeloid Sarcoma in Children: The Experience of the Polish Pediatric Leukemia and Lymphoma Study Group - Samborska, Magdalena; Barańska, Małgorzata; Wachowiak, Jacek; Skalska-Sadowska, Jolanta; Thambyrajah, Sheanda; Czogała, Małgorzata; Balwierz, Walentyna; Kołtan, Sylwia; Peszyńska-Żelazny, Katarzyna; Wysocki, Mariusz; Ociepa, Tomasz; Urasiński, Tomasz; et al. (Frontiers in Oncology, 2022)
Myeloid sarcoma (MS) is an extramedullary malignant tumor composed of immature myeloid cells. It occurs in patients with acute myeloid leukemia (AML), myelodysplastic syndrome (MDS), or chronic myeloid leukemia (CML). MS may coincide with disease diagnosis or precede bone marrow involvement by months or even years; it can also represent the extramedullary manifestation of a relapse. The aim of this study is to describe clinical characteristics of children diagnosed with MS in Poland as well as to analyze diagnostic methods, treatment, and outcomes including overall survival (OS), relapse-free survival (RFS), and event-free survival (EFS). The study also attempted to identify factors determining treatment outcomes. The study group comprised 43 patients (F=18, M=25) aged 0-18 years (median age, 10.0 years; mean age, 8.8 years) diagnosed with MS based on tumor biopsy and immunohistochemistry or identification of underlying bone marrow disease and extramedullary tumor according to imaging findings. The clinical data and diagnostic and therapeutic methods used in the study group were analyzed. In the study group, MS was most frequently accompanied by AML. The most common site of involvement was skin, followed by orbital region. Skin manifestation of MS was more common in the age group <10 years. The most frequent genetic abnormality was the t(8;21)(q22;q22) translocation. The 5-year OS probability (pOS), 5-year RFS probability (pRFS), and 5-year EFS probability (pEFS) were 0.67±0.08, 0.79±0.07, and 0.65±0.08, respectively. In patients with isolated MS and those with concurrent bone marrow involvement by AML/MDS, pOS values were 0.56±0.12 and 0.84±0.09 (p=0.0251), respectively, and pEFS values were 0.56±0.12 and 0.82±0.08 (p=0.0247), respectively. In patients with and without the t(8;21)(q22;q22) translocation, pEFS values were 0.90±0.09 and 0.51±0.14 (p=0.0490), respectively. MS is a disease with a highly variable clinical course. Worse treatment outcomes were observed in patients with isolated MS compared to those with concurrent bone marrow involvement by AML/MDS. Patients with the t(8;21)(q22;q22) translocation were found to have significantly higher pEFS. MS location, age group, chemotherapy regimen, surgery, and/or radiotherapy did not have a significant influence on treatment outcomes.